2020
DOI: 10.1507/endocrj.ej20-0083
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective multicenter study of bone mineral density in adolescents and adults with Turner syndrome in Japan

Abstract: Osteoporosis is one of the clinical features of women with Turner syndrome (TS). The reasons for low bone mineral density (BMD) and increased bone fragility are multifactorial, including estrogen deficiency, X-chromosome abnormalities, and environmental factors. Few, large-scale studies on bone mineral density in either adolescents or adults with TS have been done in Japan. The goal of the present study was to investigate spinal BMD in women with TS, assess its relationship with clinical parameters, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(43 reference statements)
2
11
0
Order By: Relevance
“…A total of 103 subjects were included. The subjects of this study partially overlap with those reported in our previous study 9 . Major karyotype abnormalities were as follows: 45,X (27.2%), 45,X,i(X) or 45,X/46,X,i(X) (19.4%), 45,X/46,X,idic(X) (13.6%), 45,X/46,XX (10.7%), 45,X/47,XXX (9.7%), 45,X/46,X,r(X) (4.9%) and 45,X/46,XY (3.9%).…”
Section: Methodssupporting
confidence: 62%
See 3 more Smart Citations
“…A total of 103 subjects were included. The subjects of this study partially overlap with those reported in our previous study 9 . Major karyotype abnormalities were as follows: 45,X (27.2%), 45,X,i(X) or 45,X/46,X,i(X) (19.4%), 45,X/46,X,idic(X) (13.6%), 45,X/46,XX (10.7%), 45,X/47,XXX (9.7%), 45,X/46,X,r(X) (4.9%) and 45,X/46,XY (3.9%).…”
Section: Methodssupporting
confidence: 62%
“…We enrolled subjects with TS aged between 18 and 30 years old in part to exclude the potential effects of age‐related bone loss. We recently reported age‐dependent alterations in bone mineral density in TS aged 18 and 40 years old and found that bone mineral density was maintained during this period 9 ; therefore, age‐related bone loss did not appear to occur during this period. Using these populations, we specifically demonstrated that bone mineral density was higher in subjects with spontaneous menarche than in those without.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…ERT is known to improve BMD in patients with TS, a finding which was borne out by our own study ( 54 ), which compared the BMD Z-score measured by DXA before and after cyclic estrogen and progesterone therapy (Kaufmann therapy) in 18 patients with TS and found an increase in the BMD Z-score after the start of therapy ( 54 ). To the best of our knowledge, no other study has compared BMD before and after Kaufmann therapy in the same subjects.…”
Section: Low Bmd and Estrogen Deficiency In Patients With Turner Synd...mentioning
confidence: 91%